Donor coordination for effective government policies? Implementation of the new aid effectiveness agenda in health and education in Zambia - Stefan Leiderer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
There is a growing interest in the debate on aid effectiveness for assessing the impact of aid not only on economic growth and poverty reduction, but also on intermediate outcomes such as health and education. This paper reviews evidence from recent in-depth country work on the impact of government policies and service provision in health and basic education in Zambia, and examines to what extent new aid approaches have contributed to the observed outcomes. It finds that limited coordination and lax adherence to good aid principles undermine the effectiveness of these approaches. The discussion of the findings sheds light on the underlying political economy and incentive structures on both sides of the aid relation that lead to casual adherence to the principles for more effective aid in these new aid approaches. It argues that most of the observed coordination failures can be explained by collective action problems on the part of both donors and recipients. If the international aid effectiveness agenda is to move forward, it will have to devise adequate mechanisms to address these coordination disincentives.
Keywords: F5; F35; I18; I22; O19; 330; aid effectiveness; health; education; coordination; political economy; Entwicklungshilfe; Gesundheitsversorgung; Bildungswesen; Sambia